A framework for operative and social sustainability functionalities in Human-Centric Cyber-Physical Production Systems. (January 2020) - Pinzone, Marta; Albè, Federico; Orlandelli, Davide; Barletta, Ilaria; Berlin, Cecilia; Johansson, Björn; Taisch, Marco
Highlights: Six Functionalities of a Human-Centric CPPS are illustrated. Three levels of analysis of CPPS are defined. The CyFL Matrix aims to identify and organise performances in Human-centric CPPS. CyFL Matrix is a tool for companies interested in Human-centric CPPS' performances. Abstract: In a near future where manufacturing companies are faced with the rapid technological developments of Cyber-Physical Systems (CPS) and Industry 4.0, a need arises to consider how this will affect human operators remaining as a vital and important resource in modern production systems. What will the implications of these orchestrated and ubiquitous technologies in production – a concept we call Cyber-Physical Production Systems (CPPS) – be on the health, learning and operative performance of human workers? This paper makes three main contributions to address the question. First, it synthesizes the diverse literature regarding CPS and social sustainability in production systems. Second, it conceptualizes a holistic framework, the CyFL Matrix, and outlines a guideline to analyze how the functionalities of a CPPS relate to operational and social sustainability-related performance impacts at different levels of analysis. Finally, it presents an industrial use case, which the CyFL Matrix and the related guidelines are applied to. In doing so, the study offers first support to researchers and managers of manufacturing companies willing to define suitable operational and social sustainability-related performances for Human-centric Cyber-Physical Production Systems of the future.